Evolutions of the National Curriculum Assessment in England and Its Implications for the Assessment of the 12-year Basic Education Curriculum in Taiwan - Sheue-Mei Lu (National Taipei University of Education, 2017)
The British Education Reform Act of 1988 introduced the national curriculum and national assessment in England and Wales. The curriculum was structured into four key stages, and pupils were assessed at or near the end of each key stage (ages 7, 11, 14 and 16). The school performance tables were published to help parents make informed decisions. This article aims to present an account of the development and changes in the England national curriculum assessment from its original blueprint in 1987 to the current time through reviewing official papers, documents, and related academic articles. This article also examines the current assessment projects and programs for the 12-year Basic Education in Taiwan. Based on the recent assessment innovation efforts of the 12-year Basic Education and the assessment experience of England, the author proposes suggestions for the design and implementation of the assessment of the 12-year Basic Education Curriculum as follows: 1) Establish expected achievement standards for each learning stage based on the 12-year Curriculum Guidelines. 2)Enhance the long-term trends monitoring function of National Taiwan Assessment of Student Achievement (TASA). 3)Integrate regional TASA and remedial instruction-technology-based testing programs. 4) Re-clarify the purposes of the Comprehensive Assessment Program for Junior High School Students. 5) Plan and implement comprehensive teacher assessment policies.